Magnetic Resonance Imaging (MRI) Safety in Pregnant (A Literature Review) - Ramacos Fardela; Suci Ramda Rena; Atika Maulida; Fiqi Diyona (Lambung Mangkurat University Press, 2022)
Radiation is a beam of energy that comes from particles or photons. Based on the ability to ionize matter, radiation can be grouped into non-ionizing radiation and ionizing radiation. Ionizing radiation is radiation that can ionize the matter through which it passes. Ionizing radiation has proven useful in medicine. However, exposure to potential ionizing radiation can cause negative effects for health and heredity (genetic). Ionizing radiation also cannot be observed directly so a nuclear detector is needed as a radiation monitoring device. Medical imaging commonly used in pregnancy is Ultrasonography (USG) and Magnetic Resonance Imaging (MRI). MRI is one of the modalities in medical imaging that utilizes a magnetic field. The use of MRI during pregnancy is on the rise, because it has the ability to produce clear images of cross-sectional anatomy without ionizing radiation. Until now there has been no research that shows the dangers of using MRI for pregnancy. So that through this literature study it is hoped that the reader will be able to understand the available evidence regarding the safety of MRI during pregnancy. This literature study was carried out by the authors by collecting information or studies from previous researchers regarding the safety of using MRI in pregnancy and its effects on the fetus. In addition, the author also attaches some evidence stating that the use of MRI can be said to be safe for pregnancy, because it does not use ionizing radiation so there are minimal side effects.